Stretching-induced phase transitions in barium titanate-poly(vinylidene fluoride) flexible composite piezoelectric films. (1st March 2021) - Khan, Fariha; Kowalchik, Tim; Roundy, Shad; Warren, Roseanne
Abstract: Improving the piezoelectric performance of poly(vinylidene fluoride) (PVDF) is important for many applications, including energy harvesting. The addition of barium titanate (BaTiO3 ) nanoparticles in the polymer matrix is a popular method to facilitate β phase formation in PVDF films. For pure PVDF, mechanical drawing (i.e. stretching) has also been shown to increase piezoelectric performance. This work examines, for the first time, the combined effect of stretching and BaTiO3 addition on phase transformations in BaTiO3 -PVDF composite films. The results indicate that an alternative phase transformation mechanism occurs during the stretching of PVDF composite films. While stretching of pure PVDF films results in the conversion of non-polar α phase into the electroactive β phase, stretching of BaTiO3 -PVDF composite films results primarily in the conversion of weakly electroactive γ phase into the more electroactive β phase. Overall, stretching of BaTiO3 -PVDF films is shown to be beneficial for increasing β phase content of PVDF. Graphical abstract: Image, graphical abstract